Power system monitoring and control - Bevrani, Hassan; Watanabe, Masayuki (Electrical engineer); Mitani, Yasunori (Hoboken, New Jersey : Wiley, 2014)
"Providing full coverage of the basic principles on the subject, Wide Area Power System Monitoring and Control highlights key technologies for monitoring, protection, and control. The strong author team explores a host of cutting-edge topics, including renewable energy sources, smart grids, wide area stabilizing, as well as coordinated voltage regulation and angle oscillation damping. Complemented by end-of-chapter problems and solutions, as well as case studies, this comprehensive handbook provides engineers/operators and graduate students with an in-depth overview of WPSMC understanding, analysis, synthesis, and implementation"--
"The book is a reference for researchers and engineers working on power system control and operation"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Electric power systems -- Control; TECHNOLOGY & ENGINEERING / Power Resources / Alternative & Renewable; Electric power systems -- Control; Electronic books; Electronic books